Cervical Cancer Screening Program in Rangpur Medical College Hospital: 11 Years Experience (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: Prevention of cervical cancer is the easiest with regular screening tests and follow up. CIN is a pre-malignant condition, detection of which is possible by VIA and colposcopy.Objective: To identify the performance of Cervical Cancer Screening Program in Rangpur Medical College Hospital through 11 Years.Methods and materials: Apparently healthy, married or sexually active women (>10 years) and women aged >30 years attending Gynae OPD were included in this study. After counseling and informed consent a speculum examination was performed for direct visualization of cervix to identify the squamo-columner junction. Freshly prepared 5% acetic acid was applied to the cervix for one minute. All the VIA positive women were further evaluated by colposcopy. Women with negative VIA were advised for 3 yearly VIA test. Suspected CIN cases were evaluated by colposcopy guided punch biopsy or LEEP biopsy and histopathology.Results: VIA screening was provided for 11,792 women from August 2005 to August 2016 and 932 (7.9%) were positive VIA. From November 2007 to August 2016, total women underwent colposcopy were 1548. Among them 632 (40.8%) were normal, out of abnormal cases 730 (80.3%) were CIN-1, 147 (16.1%) were CIN-2, 14 (1.5%) were CIN-3, 17 (1.8%) were invasive and 8 (0.5%) were unsatisfactory. From November 2007 to August 2016 punch biopsy was taken in 384 women and total 568 women were treated by LEEP.Conclusion: In a low resource setting like Bangladesh VIA and colposcopy can detect 80% pre-invasive cervical lesion and may be one of the most important tool to prevent cervical cancer and its mortality.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 11-16